Možnosti ocenjevanja depresivne simptomatike pri bolnikih z afazijo znotraj rehabilitacijskega tima - pilotna raziskava - Mlinarič Lešnik, Vesna (Rehabilitacija (Ljubljana), 2019)
Background: Depression is common in patients who experience speech and language problems after stroke. Our pilot study evaluated the measurement characteristics of the Slovene translation for the Aphasic Depression Rating Scale (ADRS), a rating scale designed for members of the rehabilitation team. Methods: We included eight patients with aphasia. Members of the rehabilitation team who were in daily contact with the patient (registered nurse, occupational therapist and physiotherapist) completed the ADRS for each patient. Results: We observed a low degree of agreement between the rehabilitation team members. Conclusion: The comparison of ratings showed low inter-rater reliability. The scale should therefore be further adapted so that it could be used by different professionals within the rehabilitation tem.
Keywords: ADRS; afazija; Aphasia; Aphasic Depression Rating Scale; depresija; depression; lestvica za oceno depresivnosti pri bolnikih z afazijo; možganska kap; rehabilitacijski tim; rehabilitation; rehabilitation team; stroke